Application Failure Mode Effect Analysis for Risk Management in New Costumer Acceptance Project in Garment Industry with approaching Project Management Body of Knowledge - Rahmawati, Diah; Redi , A.A.N. Perwira (Journal of Entrepreneurship and Business, 2023)
Purpose: This research aims to identify risks at the time of fulfillment of the requirements set by the customer and determine their mitigation. Method: In order to achieve the goal, researchers use the PMBOK approach that focuses on risk management by creating WBS and RBS. From the existing risks assessed using the FMEA method by conducting a survey to get the S, O and D values then calculating the RPN. Result: the highest RPN value in this study is 330 at risk 5.2. The understanding of PIC system and procedures in making the system, based on the result of brainstorming is decided that the mitigation is recruiting employee who is experienced in applying BSCI and factory evaluation audits due to the unavailability of employees who will become PIC compliance.